Optimisation of supply chain performance using MCDM tool – a case study. (9th June 2010) - Parthiban, P.; Mathiyalagan, P.; Punniyamoorthy, M.; Dominic, P.D.D.
The core of operations research is the development of approaches for optimal decision-making. A prominent class of such problems is multi-criteria decision-making (MCDM) and the typical MCDM problem deals with the evaluation of a set of alternatives in terms of a set of decision criteria. One such method used to evaluate the alternatives on the basis of criteria is ELECTRE method. A case study is taken up on a retailer shop where the supply chain i.e., distributor-retailer-customer is encountered. The objective as how to select the best supplier for each of the three products taken up is achieved using the ELECTRE method. The best alternative is found out using the method doing the pair wise comparisons under each criterion separately.